A simple approach for the computation of magnetic characteristics of 4-phase switched reluctance motor - Hadapad, Basavaraju S.; Naik, Raghuram L. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Switched reluctance motor (SRM) is non-linear in nature due to non-uniform air gap between stator and rotor that is produced from doubly salient poles. To control the operation of non-linear motor, a precise modelling of magnetic characteristic is essential. Traditionally magnetic equivalent circuit, finite element method (FEM) and experimental approaches have been used to derive magnetic characteristics of SRM. These methods involve complex computational steps and numerous assumptions for its calculations. To avoid this complexity, a simple approach is suggested in this paper to compute magnetic characteristics of 4-phase SRM. In this approach, SRM phase inductance is measured directly to identify the location of rotor with respect to stator from unaligned to aligned position. Then, single phase of SRM is excited through asymmetric converter and voltage and currents of corresponding phase is recorded with rotor being blocked using indexing head. Later recorded values are used to compute the magnetic characteristics from unaligned to aligned position. The proposed method is carried out using field programmable gate array (FPGA) controlled 8/6, 4-phase SRM. Further, accuracy of obtained magnetic characteristic is verified using FEM. In addition, fidelity of the magnetic characteristic is also validated by developing a dynamic model of SRM in MATLAB/Simulink